2017
DOI: 10.1371/journal.pone.0177790
|View full text |Cite
|
Sign up to set email alerts
|

No evidence that migratory geese disperse avian influenza viruses from breeding to wintering ground

Abstract: Low pathogenic avian influenza virus can mutate to a highly pathogenic strain that causes severe clinical signs in birds and humans. Migratory waterfowl, especially ducks, are considered the main hosts of low pathogenic avian influenza virus, but the role of geese in dispersing the virus over long-distances is still unclear. We collected throat and cloaca samples from three goose species, Bean goose (Anser fabalis), Barnacle goose (Branta leucopsis) and Greater white-fronted goose (Anser albifrons), from their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Recent studies (Si et al, 2009;Tian, Zhou, Dong, Van Boeckel, Cui, et al, 2015) have suggested that long-distance migration of wild birds may be responsible for the huge geographic jumps of HPAI H5N1 between continents (Yin et al, 2017). Wild birds, however, may influence the spread of HPAI H5N1 in complex ways.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies (Si et al, 2009;Tian, Zhou, Dong, Van Boeckel, Cui, et al, 2015) have suggested that long-distance migration of wild birds may be responsible for the huge geographic jumps of HPAI H5N1 between continents (Yin et al, 2017). Wild birds, however, may influence the spread of HPAI H5N1 in complex ways.…”
Section: Introductionmentioning
confidence: 99%
“…Combining the findings from the model and the empirical study, we can conclude that migrants may not exclusively affect the AIV infection dynamics of resident populations through their often suggested role in the introduction of new virus strains (e.g. Lycett et al, 2016;Verhagen et al, 2015) and the general increase in hostdensities (Gaidet et al, 2012;Hill et al 2016), but may have an additional role in the amplification of the virus (Yin et al, 2017). Since migration is a large-scale multi-species phenomenon, this might more generally be the case and it questions the hypothesis that migrants only have a role in dispersing and introducing AIVs and thereby affecting resident populations.…”
Section: Discussionmentioning
confidence: 70%
“…Lycett et al., ; Verhagen et al., ) and the general increase in host‐densities (Gaidet et al., ; Hill et al. ), but may have an additional role in the amplification of the virus (Yin et al., ). Since migration is a large‐scale multi‐species phenomenon, this might more generally be the case and it questions the hypothesis that migrants only have a role in dispersing and introducing AIVs and thereby affecting resident populations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the global dispersal of H5 subtype is spatially and temporally correlated with bird migration (Verhagen et al 2015;Si et al 2009;Xu et al 2016). Furthermore, previous studies have also shown that the arrival of migratory waterfowl species such as mallard Anas platyrhynchos, greater white-fronted goose Anser albifrons, and whooper swan Cygnus cygnus on their overwintering site can amplify AIVs infection prevalence Yin et al 2017;Newman et al 2009).…”
Section: Migration Affects Pathogen Dynamicmentioning
confidence: 99%
“…Since the risks for HPAIVs outbreaking are high when the HPAIVs are dispersed into a new location, a better understanding of their dispersal mechanisms is urgently needed for planning better field surveillance programs Verhagen et al 2015;Xu et al 2013) and predicting HPAIV outbreaks Prosser et al 2013). Meanwhile, since LPAIVs are predecessors for HPAIVs, understanding of their dispersal mechanisms is urgently necessary as well (Cappelle et al 2014;Yin et al 2017).…”
Section: Short Introduction Of Avian Influenza Virusmentioning
confidence: 99%